Financial Consumer Protection and Fintech : An Overview of New Manifestations of Consumer Risks and Emerging Regulatory Approaches - World Bank (Washington, DC, 2022)
This note provides: (1) an overview of new manifestations of consumer risks that are significant and cross-cutting across four key fintech products: digital microcredit, P2PL, investment-based crowdfunding, and e-money; and (2) examples of emerging regulatory approaches to target such risks. This note is based on a more detailed recently published WBG Policy Research Paper titled Consumer Risks in Fintech, New Manifestations of Consumer Risks and Emerging Regulatory Approaches. The research paper delves more deeply into each of the four key fintech products and their associated risks. The appendix provides an overview of product-specific risks for which more information can be found in the research paper. The primary focus and objective of this note, and the paper on which it is based, is to inform authorities’ development of regulatory policy. The examples included here are intended to assist regulators considering potential FCP regulatory approaches to fintech. However, it is hoped that the discussion of manifestations of consumer risks in a fintech context can also assist authorities with related key areas, such as market conduct supervision.